Anatomical and functional healing after resorbable magnesium scaffold implantation in human coronary vessels: A combined optical coherence tomography and quantitative flow ratio analysis. Issue 6 (27th November 2020) - Cerrato, Enrico; Belliggiano, Davide; Quadri, Giorgio; Erriquez, Andrea; Anselmino, Matteo; Quirós, Alicia; Franzè, Alfonso; Ferrari, Fabio; Rolfo, Cristina; Mejia‐Renteria, Hernan; Escaned, Javier; Gonzalo, Nieves; et al.
Abstract: Background: No data are currently available on the process of vessel healing and long‐term physiological results after implantation of resorbable magnesium‐made scaffold (RMS) in human coronary arteries. Objectives: To investigate after percutaneous coronary intervention (PCI) and at 12 months follow‐up (a) RMS resorption process and vessel healing, as judged by optical coherence tomography (OCT) imaging; and (b) physiological result of RMS implantation evaluated by quantitative flow ratio (QFR). Methods: All patients successfully treated with at least one RMS from July 2016 to August 2018 at 2 Italian centers were evaluated. All cases with OCT pullback and/or coronary angiography suitable for QFR analysis performed after PCI and at 12 months were included. Resorption process was analyzed at OCT in each frame reporting presence of residual struts in the vessel. Results: Forty‐four patients/forty‐nine lesions were included. 12‐months mean lumen area (LA; 7.54 ± 3.04 mm 2 ) significantly decreased compared to mean LA recorded immediately after PCI (8.12 ± 1.89 mm 2 ; p < .01). However, LA changes did not affect the functional result of PCI with a non‐ischemic QFR value (>0.80) in 98% of cases at 12‐months follow‐up. Protruding struts were detectable in more than half of cases and their presence was correlated with an increase in mean LA (+0.73mm 2 [95% CI 0.51–0.94], p < .001). Conclusions: RMS implantation in a real‐world population lead to significant decrease in mean LA without significant functional impairment. Two different patterns of RMS resorption were recorded, whose clinical significance remains to be investigated.